Trust, Temperature Fluctuations, and Asylum Applications - Stefano Carattini; Marcella Veronesi (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper studies the relationship between generalized trust, temperature fluctuations during the maize growing season, and international migration by asylum seekers. A priori generalized trust can be expected to have an ambiguous effect on migration. On the one hand, countries with higher trust may exhibit higher adaptive capacity to temperature fluctuations and so lower climate-induced migration. On the other hand, trust may also facilitate migration by increasing the likelihood that communities invest in risk sharing through migration and enjoy reliable networks supporting migrants. Hence, it is an empirical question whether trust mitigates or increases the impact of climate change on migration. Our findings are consistent with an ambivalent effect of trust on migration. We find that for moderate temperature fluctuations, trust mitigates the impact of weather on migration. This effect is driven by the role of trust in increasing adaptive capacity. However, for severe temperature fluctuations, communities with higher trust experience more migration. Overall, the former effect dominates the latter, so that the net effect is that trust mitigates migration. Our findings point to important policy implications concerning the role of trust in fostering adaptation by facilitating collective action, and the need for targeted interventions to support adaptation and increase resilience in low-trust societies in which collective action may be harder to achieve.
Keywords: O15; Q54; Z13; 330; migration; climate change; trust; adaptation